Phytochemical and Morphological Responses of Atropa (Atropa belladonna L.) to PGPR under Greenhouse Conditions - M Ineloffer; M Heidari; H Naghdi Badi; SM Tolyat Abulhassani; H Makarian; MR Ameryan (Institue of Medicinal Plants, ACECR, 2019)
Background: Atropine and scopolamine are important alkaloids that are widely used in the pharmaceutical industry. Objective: Determination of the effects of PGPR (Plant growth-promoting rhizobacteria) on phytochemical and morpho-physiological traits of Atropa belladonna L. under greenhouse conditions. Method: This study was done as a factorial experiment based on a randomized complete block design with 3 replications. PGPR in four levels including control or no inoculation, Pseudomonas, Azotobacter, Pseudomonas + Azotobacter and Thiobacillus + Sulfur as the first factor, and also chemical fertilizer at three levels including no fertilizer, 50% recommended fertilizer and 100% recommended fertilizer as second factor were used. Results: The PGPR and chemical fertilizer and their interactions had significant effect (P ≤ 0.01) on phytochemical and morpho-physiological traits. The highest values of root volume, root diameter and root dry weight were obtained from treatment of Azotobacter with 50% recommended fertilizer. The highest atropine and scopolamine levels of leaf (19.58 and 7.77 mg/g, respectively) were observed in no bacteria inoculation with 50% chemical fertilizer. The highest root atropine content was 7.69 mg/g which related to treatment of Thiobacillus + sulfur with 100% recommended fertilizer. The highest content of root scopolamine (5.69 mg/g) was observed in treatment of no bacteria inoculation with 50% recommended fertilizer. Conclusion: Generally, the results showed that PGPRs (plant growth-promoting rhizobacteria) improved the quantitative and qualitative performance of A. belladonna.